Tupperware: Sebuah Kajian Terhadap Declining Brand Besar - Hatta Firdaus; Wiwi Isnaini (Jurnal Desain Komunikasi Visual, 2026)
Using a comparative approach to the case of the decline of the Nokia brand, this study aims to examine the phenomenon of the decline of the Tupperware brand. It identifies the factors influencing the decline in brand performance, including internal changes within the company and external changes such as consumer behavior and market dynamics. This study employs a qualitative approach with comparative analysis. Data was obtained through documentary and literature research, as well as analysis of other publications and secondary sources such as scientific journals, industry reports, and relevant publications. Furthermore, descriptive analysis was conducted to identify patterns of similarities and differences between the two situations. The research findings indicate that Tupperware’s brand decline is similar to Nokia’s, particularly regarding the inability to adapt to innovation and shifting market trends. While the market shifted toward e-commerce and digital platforms, Tupperware continued to rely on traditional marketing strategies such as direct sales. Additionally, the emergence of competitors offering more diverse designs and lower prices also led to a decline in customer interest. Changes in customer preferences, which increasingly prioritize practicality, price, and product accessibility, were identified as an additional factor. This comparative analysis indicates that one of the primary causes of the brand’s decline is the company’s failure to adapt to the business environment swiftly and effectively. Amid intensifying competition, these findings are expected to assist the company in ensuring the brand’s sustainability.